Research progress on prevalence status and influencing factors of periodontal disease in the elderly - MA Tengyu, ZHAO Xida, LIU Lu (口腔疾病防治)
Periodontal disease burden is related to economic level. The burden of periodontal disease in Europe and the Western Pacific, which have higher economic levels, is lower than that in Africa and Southeast Asia. The burden of periodontal disease is mostly concentrated in people over 65 years of age. China currently has the heaviest burden of oral disease in the world; the country’s disability adjusted life years account for 18.69%. There are regional differences in the distribution of periodontal conditions that are related to socioeconomic conditions, dietary habits, and other factors of different regions. Some survey results show that the prevalence of periodontal disease among those in the middle-aged group (45-64 years old) is higher than that among the elderly group (over 65 years old). This is because the oral condition of the elderly group is prone to bias in statistics due to tooth loss and other reasons. The occurrence and development of periodontal disease in the elderly is related to a variety of factors: aging triggers physiological degeneration of periodontal tissue and decline in immune function; weakened mobility and weak oral health awareness lead to insufficient daily oral cleaning; certain systemic diseases can aggravate periodontal tissue inflammation, such as diabetes, osteoporosis, and cognitive impairment; and the cumulative impact of factors such as smoking, high-calorie diet, and nutrient deficiencies on periodontal tissue. At present, China has entered the stage of aging, which means that there is an increase in the burden of oral disease, and this puts higher requirements for the allocation of social medical resources in the future. Therefore, the prevention and treatment of periodontal disease in the elderly population is particularly important. This article, which takes the elderly over 65 years old as the research group, collects and summarizes the prevalence of periodontal disease in this group at home and abroad, and explores the influencing factors of periodontal disease in the elderly. In order to provide a basis for the early prevention of periodontal disease in the elderly, a focus must be placed on disease control and prevention as well as treatment of specific susceptible groups.